Empathy and developmental coordination disorder in adolescents and adults - an exploratory stydy - Martins, Adriana Sofia Araújo (2023)
Empathy is divided into affective and cognitive dimensions, allowing na individual to share and recognize emoticons in themselves. When there are impairments in motor coordination, these can impact the development of empathy. The aim of this dissertation is to investigate, in na exploratory manner, whether there is a relantionship between the perception of motor coordination difficulties and cognitive and affective empathy skills in adolescentes and young adults. Data were collected on motor coordination in the performance of daily tasks using the Adolescent and Adult Coordination Questionnaire (AACQ-PT) and on levels of empathy using the Questionnaire of Cognitive and Affective Empathy (QCAE), in individuals aged to 16 to 35. The results showed significant correlations between the AACQ-PT score and the subdimensions of the QCAE, as well as significant sociodemographic predictors for the subdimensions. The results indicated that the self-perception of few difficulties in motor coordination determines higher levels of empathy (p˂0.05). It was observed that females and those with a broader social network had better results in the empathy dimensions (p˂0.05). There appears to be a relantionship between self-perception of motor coordination in the performance of tasks, the size of the social network, and gender with levels of empathy.